Liver X Receptor (LXR) partial agonists: Biaryl pyrazoles and imidazoles displaying a preference for LXRβ. Issue 2 (15th January 2015) - Kick, Ellen; Martin, Richard; Xie, Yinong; Flatt, Brenton; Schweiger, Edwin; Wang, Tie-Lin; Busch, Brett; Nyman, Michael; Gu, Xiao-Hui; Yan, Grace; Wagner, Brandee; Nanao, Max; et al.
Graphical abstract